PERAN PREFERENSI TERHADAP PEMBELIAN KOSMETIK HALAL PADA PLATFORM SHOPEE DI KALANGAN MUSLIM KABUPATEN BONE - Windi Widyastuti; Ida Farida; Fitriani Fitriani (ISTISMAR, 2026)
Abstract : This study aims to determine the influence of product quality, dizcounts, price, and halal labeling on purchasing decisions for halal cosmetics on the shopee platform among Muslims in Bone Regency. This study used a quantitative approach with a survey method of 100 respondents selected using a simple random sampling technique. Data were analyzed using multiple linear regression with the help of SPSS V.26. The results showed that price and halal labeling significantly influenced purchasing decisions, while product quality and discounts did not. Simultaneously, product quality, discounts, price, and halal labeling significantly influenced purchasing decisions for halal cosmetics on the shopee platform. The coefficient of determination (R2) of 0,752 indicates that 75.25 of the variation in purchasing decisions can be explained by these four variables.